Application of silica nanoparticles to develop faujasite nanocomposite for heavy metal and carcinogenic dye degradation. (18th April 2018) - Maiti, Moumita; Sarkar, Manas; Xu, Shilang; Das, Sukhen; Adak, Dibyendu; Maiti, Soumen
Abstract : Role of Silica nanoparticles as feasible advantageous material has already been recognized due to its good thermal, low density, mechanical stability, and chemical inertia whereas industrial by product; fly ash has been also modified with different approaches for better environmental solution in recent times. In this present exertion, initially about ∼20 nm of silica nanoparticles was synthesized and characterized by XRD, Zeta size analyzer, TEM, and Fourier Transformed Infrared spectra (FTIR) spectroscopy. Furthermore, the synthesized silica NPs was impregnated in fly ash to synthesize the Faujasite materials at 50°C while various characterizations techniques (XRD, FTIR, SEM equipped with EDS) explore the developed Faujasite material are in nanodimensioned (∼200 nm) cubical shaped. The heavy metal (Lead, Chromium, and Cobalt) adsorption and degradation of dyes (Methylene blue and Methyl red) were investigated by varying different parameters (i.e., pH, temperature, Contact time, amount of Faujasite, initial concentrations of solutions). Minimum amount (1 g) of Faujasite is adequate to adsorb the heavy metal at pH 5.0 in contact time 120 min at >35°C temperature and only 20 mg of Faujasite is considered as the optimizing value for photocatalytic activity at the similar condition. Such observations suggest budgetary and ecofriendly aspects to exploit the vast resources of fly ash along with silica NPs for wastewater treatment. © 2018 American Institute of Chemical Engineers Environ Prog, 38: S15–S23, 2019